2003
DOI: 10.1080/10284150310001614661
|View full text |Cite
|
Sign up to set email alerts
|

A Diet Fortified withl-lysine andl-arginine Reduces Plasma Cortisol and Blocks Anxiogenic Response to Transportation in Pigs

Abstract: We studied the effects of diet fortified with L-lysine HCl (Lys) and L-arginine (Arg) on stress (transportation) responses in male finishing pigs (Landrace x LargeWhite x Duroc). Pigs (n = 16) were randomly divided into two equally sized groups so that the average starting body weight in the groups was identical. For 1 week immediately preceding the transportation, the first group of pigs received a control diet while the second group received a Lys and Arg fortified diet. Plasma aminogram, cortisol and body w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
14
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 19 publications
3
14
0
Order By: Relevance
“…Although histochemical studies (26,27) revealed that the predominant source of salivary chromogranin A is salivary glands themselves, this protein directly reflects the sympathetic tone and sympathetic stress response (13,21,22,38). The results agree with previously obtained human data (34) and, at hormonal level, correspond to the results reported in pigs (37). While all subjects tested in the trial were found healthy by a physician, it was assumed that most of the participating subjects were concerned with the level of mental stress in their daily lives.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Although histochemical studies (26,27) revealed that the predominant source of salivary chromogranin A is salivary glands themselves, this protein directly reflects the sympathetic tone and sympathetic stress response (13,21,22,38). The results agree with previously obtained human data (34) and, at hormonal level, correspond to the results reported in pigs (37). While all subjects tested in the trial were found healthy by a physician, it was assumed that most of the participating subjects were concerned with the level of mental stress in their daily lives.…”
Section: Discussionsupporting
confidence: 83%
“…Recent results have indicated that the essential amino acid L-lysine (Lys), which is not a direct neurotransmitters precursor, reduces anxiety (34) and normalizes stress-induced hormonal responses in otherwise healthy subjects with relatively high perceived anxiety (11) and when applied with L-arginine (Arg), blocks stress-induced pathologies in laboratory and farm animals (31,32,37). Physiological mechanism underlining the above effects is probably coupled to Lys acting as a partial serotonin receptor 4 antagonist (9,33) and simultaneously as a partial benzodiazepine agonist (2,3).…”
mentioning
confidence: 99%
“…By meeting the requirements of the transport conditions, the pig stress burden can be reduced. They are especially the conditions reported for example by Lambooy and Engel (1991), Schutte et al (1994), Fischer (1995), Troeger (1995), Perremans and Geers (1996), Geverink et al (1998), Warriss (1998b), Srinongkote et al (2003), Kozak et al (2004), Kuchenmeister et al (2005), which means especially that the careful and humane treatment of the animals, regular moving and handling, loading and unloading, mixing with unfamiliar conspecifics in the loading space, loading density, ambient temperature, transportation time, careful driving, and feeding pigs before transport. Genetic predisposition also has a significant impact on pre-slaughter pig mortality, as reported by Murray and Johnson (1998), Warriss (1998a), Werner et al (2005).…”
Section: Discussionmentioning
confidence: 92%
“…Mortality increased in pigs fed within 4 hours of transport. Srinongkote et al (2003) studied the impact of a diet fortified with L-lysine and L-arginine on the plasmatic levels of cortisol in transported pigs. In the pigs with L-lysine and L-arginine fortified diet, they determined lower plasmatic levels of cortisol than in the pigs with a diet without the addition of L-lysine and L-arginine.…”
mentioning
confidence: 99%
“…This study, which was a part of a larger wheat fortification trial, was based on a hypothesis that fortification of a lysine inadequate diet in poor communities may reduce anxiety and improve stress response, thereby potentially improving the quality of life. The hypothesis originated from studies that found worsening of stress-induced anxiety and colonic health in rats fed a lysine-deficient diet (9) and an improvement of stress responses in rats and pigs receiving lysine loads (10,11). The anxiogenic response to lysine inadequacy in rats was mediated via serotonin alterations in the central amygdala (9), the brain region functionally comparable in rodents and humans (12).…”
mentioning
confidence: 99%